2017
DOI: 10.12968/bjon.2017.26.sup20.s46
|View full text |Cite
|
Sign up to set email alerts
|

A clinical evaluation of a transparent, absorbent, adhesive wound dressing

Abstract: The performance of a transparent absorbent adhesive wound dressing (TAAWD) was observed over 7 days in five plastic surgery clinics across Germany. The study included 47 diverse postoperative linear wounds and donor sites with dry or minimal exudate levels. Data on ease of application and removal, adhesive strength, skin compatibility, conformability to the body, visual wound inspection and parameters of wound assessment were collected and analysed. At the end of the observation period, 100% of wounds were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…While 95% application adherence to the dressing was observed, two participants required a dressing change because of the presence of exudate. Safe application of the dressings for up to 7 days in linear postoperative wounds or donor sites with dry or minimal exudate levels was already described 24 . Similarly, dressing edges peeling off the skin was described in some cases but was also not negatively rated because of the hydropolymer pad remaining in situ 24 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While 95% application adherence to the dressing was observed, two participants required a dressing change because of the presence of exudate. Safe application of the dressings for up to 7 days in linear postoperative wounds or donor sites with dry or minimal exudate levels was already described 24 . Similarly, dressing edges peeling off the skin was described in some cases but was also not negatively rated because of the hydropolymer pad remaining in situ 24 .…”
Section: Discussionmentioning
confidence: 98%
“…Safe application of the dressings for up to 7 days in linear postoperative wounds or donor sites with dry or minimal exudate levels was already described. 24 Similarly, dressing edges peeling off the skin was described in some cases but was also not negatively rated because of the hydropolymer pad remaining in situ. 24 In both studies, participants maintained normal daily hygiene including showering, which may increase the occurrence of a dressing peeling off the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilpiszewska et al [74] observed that films based on carboxymethylated derivatives of starch and cellulose were transparent and elastic; however, Santos et al [75] demonstrated that biocomposites of thermoplastic corn starch and BC showed a lower transparency than pure BC, different results from those found in our study. It is important to highlight that using a transparent wound dressing allows the patient to assess the wound healing process continuously without stimulating the injured area, thus reducing the probability of secondary injuries, particularly in cases of dermal lesions [76]. Thus, the application of samples F2-F9 in clinical practice is highly relevant.…”
Section: Discussionmentioning
confidence: 99%